C-arm CT scanning combined with simple laser device-assisted puncture therapy for cerebellar hemorrhage - Chen, Yang; Li, Chenglong; Wang, Qingbo; Li, Zefu (Frontiers in Surgery, 2024)
BackgroundCerebellar hemorrhage is a severe cerebrovascular disease. The small posterior fossa space can cause compression of surrounding brain tissue with even a small amount of bleeding, leading to increased intracranial pressure, disruption of blood supply to surrounding brain tissue, and exacerbation of brain function damage. The most common surgical approach currently is craniotomy for hematoma evacuation, inevitably causing damage to surrounding nerves and blood vessels. In this study, we introduced C-arm CT scanning combined with simple laser device technology to assist in puncture drainage for cerebellar hemorrhage, aiming to improve the accuracy of surgery and maximize the protection of patients’ brain function, providing a physiological basis for better clinical prognosis.Materials and methodsFrom January 2023 to February 2024, a total of 8 patients (6 males, 2 females) with cerebellar hemorrhage underwent C-arm CT-assisted puncture therapy combined with a simple laser device at the affiliated hospital of Binzhou Medical University. Statistical analysis was performed on operation time, number of punctures, impact on important structures and vessels, postoperative hematoma clearance, complications, and neurological function recovery.ResultsAll 8 patients underwent the surgery smoothly without causing damage to important structures or blood vessels. There was no rebleeding intraoperatively. Among the 8 patients, 5 were discharged smoothly, while 3 patients opted to discontinue treatment and requested discharge. At the 3-month follow-up, 3 patients showed no ataxia, while 2 patients had impaired cerebellar motor function.ConclusionC-arm CT scanning combined with a simple laser device technology can accurately locate the position of the hematoma, effectively avoid important structures and vessels, reduce damage to surrounding normal brain tissue, and maximize the protection of normal brain tissue function. Real-time navigation and dynamic adjustments during surgery allow immediate access to imaging data postoperatively. It also has the advantages of being minimally invasive, highly precise, easy to operate, and short operation time, demonstrating high practicality and feasibility.